Historia Moldo-Vlachica: observații asupra manuscrisului, în pregătirea unei noi ediții critice - Florentina Nicolae (Revista de Istorie și Teorie Literară)
In this study we intend to present the results of the research work occasioned by transcribing Cantemir’s manuscript Historia Moldo-Vlachica for its new critical edition. The first (and only) critical edition published so far was issued in 1983 through the efforts of Professor Dan Sluşanschi, at the Academy Publishing House. After 33 years, benefiting on the one hand of experience under the guidance of the Professor, on the other hand, of higher technical requirements, we resumed the original text written by Cantemir himself to transcribe and comment it on the critical apparatus.